ChemInform Abstract: Artificial Flavin Systems for Chemoselective and Stereoselective Oxidations. Issue 16 (April 2015) - Cibulka, Radek
Abstract Review: [using hydrogen peroxide and oxygen as stoichiometric oxidizing agents; 51 refs.